Making choices in digital play spaces: Children’s experiences - Fiona M. Loudoun; Bryan Boyle; Maria Larsson-Lund (Scandinavian Journal of Occupational Therapy)
Background Digital spaces are rapidly emerging as a space for children to engage in autotelic play.Aim To explore and describe children’s experiences of choice-making in their play in digital spaces from the perspective of children themselves.Methods Focus groups were conducted with a total of eight children aged six years of age within their school, in a large city in Ireland. A Mosaic Approach with drawing, cutting, and colouring in was used to elicit the children’s voices to ensure their active engagement throughout the data collection. Data was analyzed using focus group analysis.Results Data analysis revealed three main themes; children enjoy the ability to make choices in their play, that they are often constrained in their ability to make choices, and that they negotiate ways in which they can select options for play in digital spaces.Conclusions Findings indicate that children are agentic individuals who are capable of making decisions in their play in digital spaces. This knowledge provides implications for Occupational Therapists to enhance play as an occupation in digital spaces.